Production of recombinant human G-CSF from non-classical inclusion bodies in Escherichia coli - Trinh, Nguyen Thi My (Braz J Microbiol, 2021)
Recombinant granulocyte colony–stimulating factor (G-CSF) protein produced in Escherichia coli has been widely used for the treatment of neutropenia induced by chemotherapy for decades. In E. coli cells, G-CSF is usually expressed as inactive inclusion bodies, which requires costly and inefficient denaturation and refolding steps to obtain the protein in its active form. However, following the findings of previous studies, we here successfully produced G-CSF in E. coli as non-classical inclusion bodies (ncIBs), which contained likely correctly folded protein. The ncIBs were easily dissolved in 0.2% N-lauroylsarcosine solution and then directly applied to a Ni-NTA affinity chromatography column to get G-CSF with high purity (> 90%). The obtained G-CSF was demonstrated to have a similar bioactivity with the well-known G-CSF containing product Neupogen (Amgen, Switzerland). Our finding clearly verified that the G-CSF production from ncIBs is a feasible approach to improve the yield and lower the cost of G-CSF manufacturing process.